2000
DOI: 10.1002/(sici)1097-4652(200002)182:2<171::aid-jcp5>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of p53 family members in apoptosis

Abstract: p53-mediated apoptosis involves multiple mechanisms. A number of p53-regulated apoptosis-related genes have been identified. Some of these genes encode proteins that are important in controlling the integrity of mitochondria while the others code for membrane death receptors. p53 may also induce apoptosis by interfering with the growth factor-mediated survival signals. Although the transactivation-deficient p53 can induce apoptosis, evidence suggests that both the transcription-dependent and independent functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
113
0
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(117 citation statements)
references
References 112 publications
3
113
0
1
Order By: Relevance
“…Typically, p53 is activated when DNA damage occurs or the cell is stressed. It translocates to the nucleus, where it can induce proapoptotic gene expression, such as Bax, on the mitochondrial membrane, activate the effector caspase-3 and accelerate cell death (Levine, 1997;Sheikh and Fornace, 2000). Our results showed that the expression level of Bax progressively increased when the fish was treated with PFOS (Fig.…”
Section: Discussionmentioning
confidence: 56%
“…Typically, p53 is activated when DNA damage occurs or the cell is stressed. It translocates to the nucleus, where it can induce proapoptotic gene expression, such as Bax, on the mitochondrial membrane, activate the effector caspase-3 and accelerate cell death (Levine, 1997;Sheikh and Fornace, 2000). Our results showed that the expression level of Bax progressively increased when the fish was treated with PFOS (Fig.…”
Section: Discussionmentioning
confidence: 56%
“…The tumor suppressor p53 is a major regulator of the cellular response to genotoxic stress (47)(48)(49). One way in which p53 modulates the cellular stress response is by functioning as a transcription factor to regulate the expression of genes important to cell growth arrest and apoptosis, such as p21 WAF1 , PUMA, DR5, and BAX.…”
Section: P53 Down-regulates Nsmase3 Mrna Expressionmentioning
confidence: 99%
“…[3][4][5] PUMA encodes a BH3 only domain proapoptotic protein that localizes to mitochondria and interacts with antiapoptotic Bcl-2 and Bcl-X L (1)(2)(3). It is now well established that the tumor suppressor p53 predominantly functions as a transcription factor and mediates its effects by inducing growth arrest and/or apoptosis (reviewed in Sheikh and Fornace Jr, 6 Vousden and Lu, 7 and Hofseth et al 8 ). p53 mediates its apoptotic effects by transcriptionally activating the expression of proapoptotic genes, some of which include Bax, NOXA, PUMA and DR5, whose products modulate the intrinsic and extrinsic pathways of apoptosis (reviewed in Hofseth et al 8 ).…”
Section: Introductionmentioning
confidence: 99%